2022
DOI: 10.3389/fpsyg.2022.863861
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Wellbeing of Diabetic Individuals, Prediabetics, and Non-diabetics: A Population-Based Study in Saudi Arabia

Abstract: BackgroundThe increased burden of diabetes affects the quality of life, including psychosocial problems. The study aims to compare the psychological well-being of individuals who are prediabetic, diabetic, or non-diabetic.MethodsA cross-sectional exploratory study was conducted from January to June 2016 (n = 1,019) in Al Kharj, Saudi Arabia. After consent and questionnaires were filled out, trained staff took blood samples followed by anthropometry. Chi-squared tests, one-way ANOVA, and multiple linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(56 reference statements)
2
2
1
1
Order By: Relevance
“…ndings of the current study found that there were average levels of religiosity, psychological immunity, and PWB among patients with diabetes in the Kingdom of Saudi Arabia. This result is not consistent with the results of the study conducted by Aldossari et al (2022) which indicated a poorer level of PWB among diabetics in Saudi Arabia. Moreover, the study conducted by Debono & Cachia (2007) concluded that diabetes affected the level of PWB in patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…ndings of the current study found that there were average levels of religiosity, psychological immunity, and PWB among patients with diabetes in the Kingdom of Saudi Arabia. This result is not consistent with the results of the study conducted by Aldossari et al (2022) which indicated a poorer level of PWB among diabetics in Saudi Arabia. Moreover, the study conducted by Debono & Cachia (2007) concluded that diabetes affected the level of PWB in patients.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, the results found no differences in religiosity, psychological immunity, and PWB due to the age group of patients with diabetes, and the reason may be that diabetes affects the individuals regardless of their age. This is consistent with the theoretical literature indications about the negative impact of diabetes on physical and psychological health (Alhunayni et al, 2020, Aldossari et al, 2022.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding psychological functioning, our findings are consistent with previous studies [1,9,45,46]. We found significant differences in the median scores of both men and women on the GHQ-12 in both the total score and its three dimensions.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetes is a major health burden with an increasing global prevalence [1]. It is recognised as a leading chronic disease causing disability and a main cause of mortality [2].…”
Section: Introductionmentioning
confidence: 99%